Prediction of the hidden genotype of mixed infection strains in Iranian tuberculosis patients - Mansour Kargarpour Kamakoli; Ghazaleh Farmanfarmaei; Morteza Masoumi; Sharareh Khanipour; Safoora Gharibzadeh; Christophe Sola; Abolfazl Fateh; Seyed Davar Siadat; Guislaine Refregier; Farzam Vaziri (International Journal of Infectious Diseases, 2020)
Background: Patients with mixed-strain Mycobacterium tuberculosis infections may be at a high risk of poor treatment outcomes. However, the mechanisms through which mixed infections affect the clinical manifestations are not well recognized. Evidence suggests that failure to detect the pathogen diversity within the host can influence the clinical results. We aimed to investigate the effects of different genotypes in mixed infections and determine their relationship with heteroresistance in the treatment of Iranian tuberculosis patients. Methods: One of the genotypes was identified in the culture and another genotype pattern in the mixed infection was predicted by comparing the pattern of MIRU-VNTR between the clinical specimens and their respective cultures in each patient. For all patients, the drug susceptibility testing was carried out on three single colonies from each clinical sample. The follow-up of patients was carried out during six months of treatment. Results: Based on MIRU-VNTR profiles of clinical samples, we showed that 55.6% (25/45) of the Iranian patients included in the study had mixed infections. Patients with mixed infections had a higher rate of treatment failure, compared to others (P = 0.03). By comparing clinical sample profiles to profiles obtained after culture, we were able to distinguish between major and hidden genotypes. Among hidden genotypes, Haarlem (L4.1.2) and Beijing (L2) were associated to treatment failure (6/8 patients). Conclusions: To conclude, we propose a procedure using the MIRU-VNTR method to identify the different genotypes in mixed infections. The present findings suggest that genotypes with potentially higher pathogenicity may not be detected when performing experimental culture in patients with mixed infections.